Geometrically defined environments direct cell division rate and subcellular YAP localization in single mouse embryonic stem cells - Sarah Bertels (Nature Portfolio, 2021)
Abstract Mechanotransduction via yes-associated protein (YAP) is a central mechanism for decision-making in mouse embryonic stem cells (mESCs). Nuclear localization of YAP is tightly connected to pluripotency and increases the cell division rate (CDR). How the geometry of the extracellular environment influences mechanotransduction, thereby YAP localization, and decision-making of single isolated mESCs is largely unknown. To investigate this relation, we produced well-defined 2D and 2.5D microenvironments and monitored CDR and subcellular YAP localization in single mESCs hence excluding cell–cell interactions. By systematically varying size and shape of the 2D and 2.5D substrates we observed that the geometry of the growth environment affects the CDR. Whereas CDR increases with increasing adhesive area in 2D, CDR is highest in small 2.5D micro-wells. Here, mESCs attach to all four walls and exhibit a cross-shaped cell and nuclear morphology. This observation indicates that changes in cell shape are linked to a high CDR. Inhibition of actomyosin activity abrogate these effects. Correspondingly, nuclear YAP localization decreases in inhibitor treated cells, suggesting a relation between cell shape, intracellular forces, and cell division rate. The simplicity of our system guarantees high standardization and reproducibility for monitoring stem cell reactions and allows addressing a variety of fundamental biological questions on a single cell level.